Synergistic Interactions within a Multispecies Biofilm Enhance Individual Species Protection against Grazing by a Pelagic Protozoan - Raghupathi, Prem K.; Liu, Wenzheng; Sabbe, Koen; Houf, Kurt; Burmølle, Mette; Sørensen, Søren J. (Frontiers in Microbiology, 2018)
Biofilm formation has been shown to confer protection against grazing, but little information is available on the effect of grazing on biofilm formation and protection in multispecies consortia. With most biofilms in nature being composed of multiple bacterial species, the interactions and dynamics of a multispecies bacterial biofilm subject to grazing by a pelagic protozoan predator were investigated. To this end, a mono and multispecies biofilms of four bacterial soil isolates, namely Xanthomonas retroflexus, Stenotrophomonas rhizophila, Microbacterium oxydans and Paenibacillus amylolyticus, were constructed and subjected to grazing by the ciliate Tetrahymena pyriformis. In monocultures, grazing strongly reduced planktonic cell numbers in P. amylolyticus and S. rhizophila and also X. retroflexus. At the same time, cell numbers in the underlying biofilms increased in S. rhizophila and X. retroflexus, but not in P. amylolyticus. This may be due to the fact that while grazing enhanced biofilm formation in the former two species, no biofilm was formed by P. amylolyticus in monoculture, either with or without grazing. In four-species biofilms, biofilm formation was higher than in the best monoculture, a strong biodiversity effect that was even more pronounced in the presence of grazing. While cell numbers of X. retroflexus, S. rhizophila and P. amylolyticus in the planktonic fraction were greatly reduced in the presence of grazers, cell numbers of all three species strongly increased in the biofilm. Our results show that synergistic interactions between the four-species were important to induce biofilm formation, and suggest that bacterial members that produce more biofilm when exposed to the grazer not only protect themselves but also supported other members which are sensitive to grazing, thereby providing a “shared grazing protection” within the four-species biofilm model. Hence, complex interactions shape the dynamics of the biofilm and enhance overall community fitness under stressful conditions such as grazing. These emerging inter- and intra-species interactions could play a vital role in biofilm dynamics in natural environments like soil or aquatic systems.